Faith based congestion fairness control in wireless sensor networks - TANG Wen-sheng1; PENG Yu-xing1; LI Shan-shan1; ZHANG Ding-xing1 (Tongxin xuebao)
A new basic fairness control principle was applied to assure the equal bandwidth-sharing for the link from nodes-to-sink in wireless sensor networks（WSN）.Thus,a new fairness congestion control algorithm（called EFFRC） was proposed which was based on the amounts of event information.To bypass the difficulty of calculating the amounts of event information,the algorithm calculated the size of the potential event region of the node instead of the amounts of event information.To facilitate calculating the area of the event region,it was subdivided into several quadrilateral ones,and then the area of the region was the sum of the area of all separate ones.The experiments results show that EFFRC is capable of effectively calculating event information as well as achieving the fair allocation of bandwidth.